Mathematics Learning Strategy for Discalculia Students in Elementary School - Winda Amelia; Asep Supena (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the implementation of mathematics learning for dyscalculia students, the role of teachers and parents in helping dyscalculia students in online learning, and the impact of learning strategies for dyscalculia students on mathematics learning. The research method used is descriptive qualitative method with data sources one teacher, three students, and 3 parents of students. Interactive model data analysis includes data collection, data reduction, data presentation, and drawing conclusions. Data collection techniques are observation and interviews. The results of this study indicate that teachers carry out mathematics learning by preparing Learning Implementation Plans (RPP), syllabus and special notes for students with dyscalculia. The teacher uses three learning approaches in helping dyscalculia students, namely the direct approach, group approach, and individual approach. Furthermore, the impact of the teacher's strategy in student learning with dyscalculia can be seen in the cognitive, affective, and psychomotor aspects, which have positive progress.